Efek Latihan Core Stability terhadap Peningkatan Keseimbangan pada Anak Down Syndrome: Narrative Review - Siti Atiqah Nurrahmah; Rizky Wulandhari; Asyhara Naela Arifin (Pusat riset dan Inovasi Nasional, 2026)
Down Syndrome (DS) is a genetic disorder characterized by trisomy of chromosome 21 and is inherently associated with clinical manifestations such as hypotonia, joint laxity, and neuromuscular deficits, all of which collectively contribute to impaired postural control and balance. These balance impairments significantly affect the attainment of motor milestones, performance of daily activities, and increase the risk of falls. This study aims to analyze the effectiveness of core stability training in improving balance among children with DS. A narrative review approach was employed by conducting a literature search across electronic databases including PubMed, Scopus, Google Scholar, and ResearchGate. Inclusion criteria consisted of primary studies (RCTs, quasi-experimental designs) published within the last ten years (2015–2025) that examined core stability interventions targeting balance or postural control in children with DS. A review of 10 relevant studies demonstrated that core stability training, either as a standalone intervention or combined with other modalities (e.g., treadmill training or balance training), resulted in significant improvements in both static and dynamic balance. These improvements are facilitated through the strengthening of deep trunk muscles (such as the multifidus, transversus abdominis, and rectus abdominis), which play a crucial role in proximal stabilization and force transfer to the extremities. In conclusion, core stability training is an effective and recommended intervention modality within physiotherapy rehabilitation programs to enhance the quality of life and motor independence of children with Down Syndrome.